Acclimatized apparatus enhanced seed germination in stevia rebaudiana bertoni - Abdullateef, Raji Akintunde; Osman, Mohamad; Zainuddin, Zarina (Canadian Center of Science and Education, 2015)
Stevia rebaudiana bertoni produces sweet glycosides with zero calorie and has strong health and dietary implications. With these properties, it has the potential to substitute sugar. However, poor seed germination in this plant constitute obstacle towards large scale propagation, thereby causing plant materials to be scarce and costly. High percent seed germination could be induced via simulation of favorable climatic environment. Thus, new protocols and prototype tagged ‘seed germination apparatus’, inclusive of conducive factors, were developed. Additionally, Seed viability level was also tested using 1 % tetrazolium chloride. ANOVA revealed significant differences between treatments at p < 0.05. The apparatus influenced high yield of about 67 % seed germination, while the viability test showed 69 % viable seeds. Acclimatized condition, owing to innovated seed germination apparatus, showed high impact on seed germination in stevia.